An annotated evolutionary timeline of the oxytocin signaling pathway. (September 2021) - Sartorius, A.M.; Rokicki, J.; Bettella, F.; Barth, C.; de Lange, A.-M.G.; Haram, M.; Shadrin, A.; Winterton, A.; Steen, N.E.; Schwarz, E.; Stein, D.; Andreassen, O.A.; et al.
Abstract : Introduction: Oxytocin (OT) is an ancient hormone linked to behavioral and physiological processes. Yet, the evolutionary timeline of the emergence of the OT signaling pathway and whether it has changed in primate evolution are unclear. Methods: The evolutionary age of the pathway was estimated using phylostratigraphy and gene age estimates were functionally annotated. Transcriptome Age Indices (TAI) were calculated for 5 ontogenetic stages in 16 brain regions. Natural selection of OT genes in 8 primates was assessed with substitution rate ratios. Results: 85.2 percent of the OT pathway genes emerged during 'old' phylostrata (PS) 1–3 and 11.9 percent in younger PS 4, 6 and 7. Older genes were highly expressed in contracting organs, younger genes in the brain (all p's lesser than.05). The OT pathway was under negative selection during primate evolution (mean ratio 0.17). Conclusion: We show that the OT pathway has a more ancient origin than assumed and also confirm its high conservation, also during primate evolution. The old transcriptomic age is stable across ontogeny and brain regions. Our findings support the theory that OT signaling initially took part in basic physiological functions, adapting to more complex, neural ones.